Emergence of the First Catalytic Oligonucleotides in a Formamide-Based Origin Scenario - Šponer, Judit E; Šponer, Jiří; Nováková, Olga; Brabec, Viktor; Šedo, Ondrej; Zdráhal, Zbyněk; Costanzo, Giovanna; Pino, Samanta; Saladino, Raffaele; Di Mauro, Ernesto (Chemistry (Weinheim an der Bergstrasse, Germany), 2016)
50 years after the historical Miller-Urey experiment, the formamide-based scenario is perhaps the most powerful concurrent hypothesis for the origin of life on our planet besides the traditional HCN-based concept. The information accumulated during the last 15 years in this topic is astonishingly growing and nowadays the formamide-based model represents one of the most complete and coherent pathways leading from simple prebiotic precursors up to the first catalytically active RNA molecules. In this work, we overview the major events of this long pathway that have emerged from recent experimental and theoretical studies, mainly concentrating on the mechanistic, methodological, and structural aspects of this research.
Keywords: formamide; nucleotides; původ života; Formamides; Catalysis; formamidy; oligonukleotidy; RNA; origin of life; katalýza; nucleobases; Origin of Life; Oligonucleotides